DSGE models and their use at the ECB - Frank Smets; Kai Christoffel; Günter Coenen; Roberto Motto; Massimo Rostagno (SERIEs - Journal of the Spanish Economic Association, 2010)
Bayesian dynamic stochastic general equilibrium (DSGE) models combine microeconomic behavioural foundations with a full-system Bayesian likelihood estimation approach using key macro-economic variables. Because of the usefulness of this class of models for addressing questions regarding the impact and consequences of alternative monetary policies they are nowadays widely used for forecasting and policy analysis at central banks and other institutions. In this paper we provide a brief description of the two main aggregate euro area models at the ECB. Both models share a common core but their detailed specification differs reflecting their specific focus and use. The New Area Wide Model (NAWM) has a more elaborate international block, which is useful for conditioning the euro area projections on assumptions about foreign economic activity, prices and interest rates and to widen the scope for scenario analysis. The Christiano, Motto and Rostagno (CMR) model instead has a more developed financial sector, which allows it to be used for monetary and financial scenarios and for cross checking. Based on the comparison of two models we find a broad agreement on the qualitative predictions they make, although, in quantitative terms, there are some differences. However, the perspectives provided by the two models are often complementary, rather than conflicting.
Keywords: B4; C5; E32; E50; 330; DSGE models; central banks; monetary policy; Geldpolitik; Dynamisches Gleichgewicht; Bayes-Statistik; EU-Staaten